Proceedings of the 2nd International Conference on Technology and Educational Science (ICTES 2020) 2021
DOI: 10.2991/assehr.k.210407.258
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Assessment Practice

Abstract: Due to the global outbreak of novel corona-virus disease, the teachers are demanded to carry out authentic assessments to support the 21st century learning activities, especially at junior high school level. The quality of teachers' authentic assessment practice is reflected by their authentic assessment knowledge. In accordance with it, this descriptive study is aimed at describing teachers' perceived knowledge of authentic assessment implementation and English language learning skills. Questionnaire and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Evaluation design and its application in the teaching-learning environment have recently led to a significant focus on teaching and learning English as a Foreign Language (EFL). Scholars and professionals have examined and analyzed efficient and streamlined evaluation __________  Corresponding Author: Imam Munandar (imameducator@gmail.com) Jalan Yos Sudarso No.10, Central Aceh Regency, Aceh, 24519 ©2023 by the Authors, published by Vision: Journal for Language and Foreign Language Learning https://journal.walisongo.ac.id/index.php/vision methodologies for supervising and assessing EFL education and instruction in domestic and international contexts (Archbald, 1991;Wahyuni et al, 2021;Zaim et al, 2020) who researched authentic assessment for speaking skills in the Indonesian EFL context, clearly described the application of genuine evaluation in a speaking class, emphasizing the different evaluation categories and the associated grading rubrics. Macey et al (2013) conducted a study on implementing authentic assessment and developed a practical guide in language assessment.…”
Section: Introduction mentioning
confidence: 99%
“…Evaluation design and its application in the teaching-learning environment have recently led to a significant focus on teaching and learning English as a Foreign Language (EFL). Scholars and professionals have examined and analyzed efficient and streamlined evaluation __________  Corresponding Author: Imam Munandar (imameducator@gmail.com) Jalan Yos Sudarso No.10, Central Aceh Regency, Aceh, 24519 ©2023 by the Authors, published by Vision: Journal for Language and Foreign Language Learning https://journal.walisongo.ac.id/index.php/vision methodologies for supervising and assessing EFL education and instruction in domestic and international contexts (Archbald, 1991;Wahyuni et al, 2021;Zaim et al, 2020) who researched authentic assessment for speaking skills in the Indonesian EFL context, clearly described the application of genuine evaluation in a speaking class, emphasizing the different evaluation categories and the associated grading rubrics. Macey et al (2013) conducted a study on implementing authentic assessment and developed a practical guide in language assessment.…”
Section: Introduction mentioning
confidence: 99%
“…Similarly, Koh et al (2019) reported that authentic involves higher levels of cognitive tasks and help in developing professional competences such as critical thinking, complex problem solving, creativity and innovation, effective communication and collaboration. In another development, Wahyuri et al (2020) aimed at describing teachers' perception of application of the authentic assessment during online teaching. They found that the teachers' perceived a sufficient understanding of the implementation of online authentic assessment and also that the adjusting of the materials into the required competencies would enable the students to be close with real-world.…”
Section: Introductionmentioning
confidence: 99%